Holistic Evaluation of Islamic Education Programs: Implications of the Kirkpatrick Model in Character-Based Learning - Jannah, Nur; Rosyadi, Mundir; Mislikhah, Siti; Hadi, Sofyan (FALASIFA : Jurnal Studi Keislaman, 2025)
Evaluation of Islamic Religious Education (PAI) learning programs often emphasizes only the cognitive aspects, neglecting the affective and spiritual dimensions, which are crucial for Islamic character formation. This gap highlights the need for a model that encompasses behavioral and spiritual transformation. Kirkpatrick's model, with its four levels of reaction, learning, behavior, and outcomes, offers a comprehensive framework. This study examines its relevance for PAI evaluation, with its novelty in contextual adaptation through the integration of Islamic values ​​such as muraqabah (introspection) and ikhlas (sincerity) to authentically measure spiritual change. Using descriptive qualitative methods through literature analysis, the results show that this model encompasses PAI dimensions from perception to social impact. Despite challenges in affective measurement, the model is relatively effective when adapted. Its integration strengthens PAI evaluation toward transformative education. Practically, this implies that the development of instruments such as behavioral rubrics and tracking for the curriculum can have an impact. However, this research is limited to a literature review and has not been empirically tested in a real-world setting.